· · · · 21 2017 11:50:15



FAQ







...
...
...


: 1


: 33
: tgolovko2010

@Mail.ru
-
- :
(K,+,-) O(,+), O=e
1 aK: a*0=0*a=0; a*0=a*(0+0)=a*0+a*0; -(a*0)+a*0=-a*0+a*0+a*0; a*0=0*a
2 (ab)=(-a)b=a(-b); (-a)b+ab=(-a+a)b=0b=0. (-a)b ab (-a)b=-ab
3 a(b-c)=ab-ac; b-c=b+(-c); a(b-c)=a(b+(-c))=ab+a(-c)=ab+(-ac)=ab-ac
(K,+,) . . . . (, ) , . .
.
.
.

, .

.






?
.

?
.
...
59

51
5.10. ...
...
...
...
5.3. ...
5.7. ...
20
4.1. ...
5.18. ...

#5 ...
64
66
29
...
3.2. ...
3.3.2. ...

34
5.12. ...
" ...
4. ...
62
...

27
5.14. ...
5.7. ...
2.4.1. ...
5.7. ...
...
...

5.7. ...

5.15. ...